👤

​What is the result when​ ​2x​ 2 ​ + 3x - 1 is subtracted from 4x​ 2​+ 7x - 3?​

Sagot :

Answer:

[tex]-2x^2-4x+2[/tex]

Step-by-step explanation:

[tex]\left(2x^2+3x-1\right)=2x^2+3x-1\\[/tex]             [tex]=2x^2+3x-1-\left(4x^2+7x-3\right)[/tex]

[tex]-\left(4x^2+7x-3\right)=-4x^2-7x+3[/tex]      [tex]=2x^2+3x-1-4x^2-7x+3[/tex]

[tex]=2x^2-4x^2+3x-7x-1+3\\[/tex]            add : [tex]-1+3=2[/tex]  

[tex]=2x^2-4x^2+3x-7x+2[/tex]          then,[tex]\mathrm{Add\:similar\:elements:}\:2x^2-4x^2=-2x^2[/tex]

[tex]=2x^2-4x^2+3x-7x+2[/tex]          [tex]\mathrm{Add\:similar\:elements:}\:3x-7x=-4x[/tex]

[tex]=-2x^2-4x+2[/tex]